A low energy tunable pulsed X-ray source based on the pseudospark electron beam - Wong, C.S.; Woo, H.J.; Yap, S.L. (Cambridge University Press, 2007)
A low energy pulsed X-ray source with 17 J electrical input energy has been constructed based on the vacuum spark configuration triggered by the pseudospark electron beam. With such a low input electrical energy, the frequently studied X-ray emitting vacuum spark plasma is not obtained. Instead, this configuration gives rise to a point-like electron beam-target pulsed X-ray source at the tip of the anode. Emission of X-ray is observed during the pre-breakdown phase. The X-ray spectrum is dominated by the characteristic line emission of the anode material. The total X-ray energy emission from the source can be estimated by assuming it to be a monochromatic point source. It is found to have an X-ray production efficiency of 0.1%, giving an average X-ray dosage of 18 mGy per pulse. X-ray radiography of small biological sample is demonstrated to illustrate a potential application of the present X-ray source.